Novel Pyrazino[2,3-b] Pyrazines as mTOR Kinase Inhibitors for Treating Cancer and other Diseases - De, Surya K. (Current Medicinal Chemistry, 2024)
This paper describes the synthesis of some heteroaryl compounds and compositions comprising an effective amount of one or more such compounds and methods for treating or preventing cancer, inflammatory conditions, immunological conditions, metabolic conditions and conditions treatable or preventable by inhibition of a kinase pathway, comprising administering an adequate amount of a heteroaryl compound to a patient in need thereof. These compounds are mTOR/PI3K/Akt pathway inhibitors.
Keywords: mammalian target of rapamycin